Organic anion transporters and their influence on the toxicity of β-lactam antibiotics - V. A. Evteev; O. V. Muslimova; I. A. Mazerkina; N. D. Bunyatyan; E. V. Shikh; R. E. Kazakov (Безопасность и риск фармакотерапии, 2018)
This review article describes the classification and mechanism of action of organic anion transporters (OAT). The influence of certain members of this family of transporters on the pharmacokinetics of β-lactam antibiotics.